Present and future of risk disclosure in Spanish non-financial listed companies - María Teresa Amezaga-Alonso; Ernesto Cilleruelo-Carrasco; Enara Zarrabeitia-Bilbao; Patxi Ruiz-de-Arbulo-López (Revista de Contabilidad: Spanish Accounting Review, 2020)
This paper researches the reasons and expected benefits of Spanish non-financial listed companies for disclosing risk information as well as the possible motivations for not doing so. It investigates the current situation of risk disclosure but also looks forward and studies what it will be like in the near future. In view of an increasingly information demanding environment, it looks for ideas for improving the risk disclosure practice. With the objective of gathering insights from the parties involved (preparers and users of risk information) and getting an agreed view among them, we conducted a Delphi study. The group of experts was made up of twenty-two people, thirteen internal audit directors from Spanish non-financial listed companies, five financial analysts and four scholars. We ran three rounds of questions between the months of January and July of 2017. The study concludes, among other findings, that the demand for risk disclosure will increase in coming years, that the benefits of disclosing offset any kind of associated costs, and that the policy maker should develop more legal provisions to ensure greater clarity and consistency of risk information and more comparability among companies.